Characteristics of Implementing Organizations in the Implementation of Investment Policy (Case study in Garut Regency) - Widaningsih Widaningsih; Alian Natision; Marti Dewi Ungkari; Husni Muharam (Yayasan Ilomata, 2023)
The Endowment Development Strategy paradigm is one of the keys to success in carrying out development in our country. In the principles of the Endowment Development Strategy, one way to market the regional economic power is by opening up investment opportunities. However, the reality that has occurred regarding the development of investment in various regions (especially in Garut Regency) is still very far from expectations, where investment interest with investment realization is still far from the targeted figure. As for the purpose of this research is to find objective facts in the hope that the results of the research can be accepted as the truth. The research method used is a qualitative approach method with the object of institutional research, as well as the unit of analysis in this research is the DPMPT and other related Technical Services. The data analysis technique uses the triangulation method by synchronizing the data obtained among one informant and other informants. The results of the study show that existing SOPs at other Technical Services have not been integrated into the DPMPT so that they are still implemented partially. Based on field results there are still problems related to delays in issuing permits, this shows that the principle of excellent service, service that is fast, precise, certain, efficient and effective in accordance with the principles of good governance have not been maximized. The characteristics of implementing organizations in Garut Regency are still relatively weak, this is indicated by the unpreparedness of the human resources of the policy implementer, this is proved by the lack of understanding of the main tasks and functions (TUPOKSI) as well as Standards and the objectives of the policy itself. Based on this research, it is suggested that the implementing apparatus in the field should be involved in technical meetings in the context of integrated licensing services in order to understand the real purpose of the integrated licensing services policy. Building good and effective communication so that policy implementers have the courage to ask superiors about things they do not understand, especially about the objectives of the policies being implemented, the leaders must display a more responsive attitude, not arrogant and not authoritarian.